PENGARUH DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI HOTEL BALI NIKSOMA BOUTIQUE BEACH RESORT - James Adolf Paparang; A.A Ketut Sri Asih; Gusti Ayu Putu Suharti Cahya (Journal Research of Management, 2020)
Employee performance is a very important thing that needs to be considered in a company, because with good employee performance will certainly have a good impact on the company and will achieve the goals of the company itself. The problem raised in this study is whether work discipline (X1) affects employee performance (Y) at Bali Niksoma Boutique Beach Resort Hotel, does communication (X2) affect employee performance (Y) at Bali Niksoma Boutique Beach Resort Hotels, How the influence of work discipline and communication on employee performance at Bali Niksoma Boutique Beach Resort, and which independent variables have the dominant influence on employee performance at Niksoma Bali Hotels Boutique Beach Resort The population in this study amounted to 150 people. This study uses a sample of 60% of the population or as many as 90 people. The data analysis technique used was descriptive analysis, data quality test, classic assumption test, multiple regression analysis, t-test analysis, test analysis of the dominant variable influencing (β), and determination analysis. The results of the analysis show a regression model Y = 3.364 + 0.548X1 + 0.376X2. The conclusion obtained is that work discipline (X1) has a positive and significant effect partially on employee performance (Y) in Bali Niksoma Boutique Beach Resort Hotel which is shown by the regression coefficient b1X1 which is positive at 0.548, with the value calculated = 12.396> t table = 1.663 with sig.t = 0,000. Communication (X2) has a positive and significant effect partially on employee performance (Y) in, Bali Hotel Niksoma Boutique Beach Resort which is shown by the coefficient b2X2 which is positive at 0.376, with a value calculated = 9.576> t table = 1.663 with the value sig.t = 0,000. The independent variable which has dominant influence on employee performance can be seen in the Standardized Coefficients Beta value is the work discipline variable (X1) that is equal to 0.623 while the communication variable (X2) is 0.481. The magnitude of the influence of work discipline and communication on employee performance at the Bali Niksoma Boutique Beach Resort Hotel is 80.0% and the remaining 20.0% is influenced by other variables not discussed in this study.Keywords: work discipline, communication, and employee performance.